(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The interview with Margarita Beatriz Flores Miranda discusses her trajectory as an architect, researcher, professor of higher education in architectural projects and founder of Acto School, located in Mexico City (Mexico). The interviewee discusses her quest to develop creativity through new practices, above all, through her proposal of teaching a componential model of creative potential, which is based on four essential skills: affection, cognition, will and empathy. In this context, Margarita highlights that creativity is related to self-confidence and self-knowledge.